Analysis and Design of an Effective Light Interference Methane Sensor Based on Three-Dimensional Optical Path Model. (10th July 2018) - Long, Teng; Li, En; Yang, Lei; Fan, Junfeng; Liang, Zize
Abstract : As an important environmental monitoring equipment, the existing methane sensors or the traditional interferometer-based methane detectors have some drawbacks, such as low accuracy, large size, and complex calibration operations. Moreover, the optical path model and analysis method for the light interference methane sensor are not practical. In this paper, an effective light interference methane sensor is proposed based on a three-dimensional optical path model with point light source. Based on this model, the interference optical system is studied to illustrate the cause of the interference fringes. Furthermore, the influencing factors of the light intensity distribution are analyzed and an adjustment method for the interference fringes is proposed, which helps to simplify the assembling and calibrating operations. In order to improve the measurement accuracy, a temperature drift compensation method which includes a mapping table, a steady-state compensator, and a dynamic compensator is proposed. The mapping table is established between the output voltages of photoelectric detector, and the methane concentration, the steady-state compensator, and the dynamic compensator are proposed to eliminate the temperature drift. Finally, an experimental device for the light interference methane sensor is constructed to validate the interference fringe adjustment method and the temperature drift compensation method.